JENIS KELAMIN DAN ADAPTABILITAS KARIER: BUKTI EMPIRIS PADA MAHASISWA JABODETABEK DI ERA DINAMIKA DUNIA KERJA - Yohana Sri Rahayu; William Gunawan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Career adaptability refers to an individual's capacity to proactively cope with and adjust to challenges in career development. This study aims to examine gender differences in career adaptability among undergraduate students in the Greater Jakarta area (Jabodetabek). Despite the region's high labor market dynamics, research on students' adaptive readiness remains limited. Moreover, the use of the Career Adapt-Abilities Scale–Short Form (CAAS-SF) within the Indonesian context is still rare, highlighting a methodological gap addressed in this study. A total of 507 undergraduate students from various public and private universities participated in this study, which is part of the "Membangun Generasi Muda Mandiri" (MGMM) research program. A quantitative comparative approach was employed using the CAAS-SF with a 6-point Likert scale. The results of the independent samples t-test showed no significant difference in career adaptability between male and female students (p = 0.165). Overall, the students demonstrated a high level of career adaptability, reflected across all four dimensions: concern, control, curiosity, and confidence. These findings suggest that gender is not a primary determinant of students' career adaptability. Practically, this study provides an empirical foundation for developing inclusive and gender-equitable career services in higher education institutions, particularly in metropolitan areas like Jabodetabek, by focusing on strengthening adaptability dimensions rather than differentiating interventions by gender. ABSTRAK Adaptabilitas karier adalah kemampuan individu untuk menghadapi dan menyesuaikan diri terhadap tantangan dalam perkembangan karier secara proaktif. Penelitian ini bertujuan untuk menguji perbedaan adaptabilitas karier berdasarkan jenis kelamin pada mahasiswa S1 di wilayah Jabodetabek. Kawasan ini memiliki dinamika pasar kerja yang tinggi, namun penelitian mengenai kesiapan adaptif mahasiswa masih terbatas. Penggunaan Career Adapt-Abilities Scale–Short Form (CAAS-SF) dalam konteks Indonesia juga belum banyak dilakukan, sehingga studi ini mengisi celah metodologis yang ada. Sebanyak 507 mahasiswa dari berbagai perguruan tinggi negeri dan swasta terlibat dalam penelitian ini, yang merupakan bagian dari program Membangun Generasi Muda Mandiri (MGMM). Pendekatan yang digunakan adalah kuantitatif komparatif dengan instrumen CAAS-SF skala Likert 6 poin. Hasil uji independent samples t-test menunjukkan tidak ada perbedaan signifikan adaptabilitas karier antara mahasiswa laki-laki dan perempuan (p = 0,165). Tingkat adaptabilitas karier mahasiswa secara keseluruhan tinggi, termasuk pada keempat dimensinya: concern, control, curiosity, dan confidence. Hasil ini menunjukkan bahwa jenis kelamin bukan penentu utama dalam perbedaan adaptabilitas karier mahasiswa. Secara praktis, temuan ini menjadi dasar pengembangan layanan karier yang setara dan responsif terhadap kebutuhan mahasiswa di wilayah metropolitan, tanpa membedakan berdasarkan jenis kelamin.